Boundary-value problem for a mixed parabolic-hyperbolic equation of the third order - Eleev, V. A. (Ukrains’kyi Matematychnyi Zhurnal, 1995)
The unique solvability of a certain boundary-value problem is proved for a mixed parabolic-hyperbolic type equation of the third order.